2013
DOI: 10.1515/sg-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and efficiency of early selection for half rotation-aged growth and form traits in Pinus taeda in China

Abstract: Genetic parameters for height (H), diameter at breast height (DBH), stem straightness (STR), and under crown clear bole height (CH) of loblolly pine (Pinus taeda L.) were estimated for 255 families (209 open pollinated (OP) and 46 controlled pollinated (CP) families) using a family model and an individual tree model at age 1, 2, 3, 5, 11, and 15 years. Heritability estimates for growth traits of individual trees at age 11 years were the highest (0.17-0.78), and those at age 15 years were the lowest (0.05-0.74)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…1). Yang et al (2013) showed the first years are important to plant recover the root system and adapt to the new environment, if it does not occur, mortality rate of seedlings may be high, as observed in PG. Furthermore, lack of water in first weeks after planting may be responsible by plant mortality, the first month after planting there was less rainfall in relation to the normal April month at PG.…”
Section: Individual Deviance Analysis and Genetic Parameters Estimationmentioning
confidence: 98%
“…1). Yang et al (2013) showed the first years are important to plant recover the root system and adapt to the new environment, if it does not occur, mortality rate of seedlings may be high, as observed in PG. Furthermore, lack of water in first weeks after planting may be responsible by plant mortality, the first month after planting there was less rainfall in relation to the normal April month at PG.…”
Section: Individual Deviance Analysis and Genetic Parameters Estimationmentioning
confidence: 98%
“…The location of this trial could be categorized as a marginal site for white jabon, and according to Wahyudi (2012), the economical rotation could be reached at 13 years. The next evaluation would be carried out at 5 and 6 years (half rotation age) predicted that the growth would be more stable (Yang et al 2013).…”
Section: Balanites Aegyptiacamentioning
confidence: 99%
“…This may have been due to the fact that the growth of HT is more affected by leaf area after the forest was closed. Large effects of genotype × environment interactions on growth traits have been reported in other studies [29,38,39].…”
Section: Discussionmentioning
confidence: 56%
“…Potential contributing factors include differences in the studied species, competitive pressures, growth phases, and silvicultural factors, but further investigation is needed to clarify this issue [30]. The most widely used model for exploring age-age genetic correlations is that of Lambeth (1980), which has been tested by several researchers working on tree species [7,30,39,45]. The age-age genetic correlations were generally stronger than the corresponding phenotypic correlations, in agreement with observations on Larix principis-rupprechtii [30].…”
Section: Discussionmentioning
confidence: 99%